Peran Kepemimpinan Bupati Serdang Bedagai Ir. H. Soekirman dalam Mengembangkan Program Literasi di Kabupaten Serdang Bedagai - Agus Marwan; R Hamdani Harahap; Amir Purba (PERSPEKTIF, 2020)
Serdang Bedagai has successfully developed a literacy program. This success has led to Serdang Bedagai receiving the Literacy Award from the Ministry of Education and Culture in 2017. This success cannot be separated from the leadership role of Ir. H. Soekirman as Regent of Serdang Bedagai. There are two main roles of the Regent's leadership, Ir. H. Soekirman, in developing the literacy program in Serdang Bedagai. First, it acts as a literacy model. Soekirman has set an example by his fondness for reading books, writing books, writing rhymes and poetry. Every year he reads at least 6 books, and has produced 12 of his own. Second, it acts as a policy maker to make programs related to literacy. With his role, Soekirman has established local regulations related to literacy, Decree of the Literacy Program Implementation Team, Library Development Decree, and budget allocation policy for literacy